Growing evidence of the use and utility of climate services for smallholder farmers: A summary of recent findings from the CCAFS flagship on climate services and safety nets - Vaughan, Catherine (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2022)
This brief presents evidence generated in projects conducted in Africa and Latin America to answer these questions. Instead of an exhaustive review, this brief offers an exploration of evidence generat-ed by a few projects. While this evidence is useful for investments in areas the specific projects stud-ied, it can also help improve other actions – for instance, the implementation of services in oth-er areas; investment in National Meteorological Services; defining an appropriate balance of invest-ment in the production, translation, transfer and use of climate information; and shaping the role that climate services play in national adaptation and climate finance planning, among other things.